A Model of EFL Listening Materials Development - Mochamad Zaenuri (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2015)
In oral communication, listening skill is important because communication does not take place successfully if the message stated is not understood. To master the skill, learners should learn it. Therefore, good listening materials are needed. However, English teachers often find it difficult to teach listening skills because the listening materials are not adequately available. Besides, if the materials are available, they are not appropriate with the students’ needs and the curriculum. In that case, English teachers need to develop listening materials by themselves. For this, they should have knowledge of materials development. This paper presents ideas and tips for English teachers how to develop good and applicable listening materials.